2002
DOI: 10.1037/0033-2909.128.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Older age, traumatic brain injury, and cognitive slowing: Some convergent and divergent findings.

Abstract: Reaction time (RT) meta-analyses of cognitive slowing indicate that all stages of processing slow equivalently and task independently among both older adults (J. Cerella & S. Hale, 1994) and adults who have suffered a traumatic brain injury (TBI; F. R. Ferraro, 1996). However, meta-analyses using both RT and P300 latency have revealed stage-specific and task-dependent changes among older individuals (T. R. Bashore, K. R. Ridderinkhof, & M. W. van der Molen, 1998). Presented in this article are a meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 136 publications
(416 reference statements)
5
47
0
Order By: Relevance
“…This increased imbalance is consistent with Bashore and Ridderinkhof's (2002) speculation that TBI would have a stronger impact on non-lexical than on lexical dimensions. In our study, this increase was also found to contribute significantly to the TBI-related increase in Ci, suggesting that increased competition between retrieval of the color-and the lexical-code for TBI patients may inflate SI (see Ben-David & Schneider, 2009, for studies on aging in this respect).…”
Section: Discussionsupporting
confidence: 87%
“…This increased imbalance is consistent with Bashore and Ridderinkhof's (2002) speculation that TBI would have a stronger impact on non-lexical than on lexical dimensions. In our study, this increase was also found to contribute significantly to the TBI-related increase in Ci, suggesting that increased competition between retrieval of the color-and the lexical-code for TBI patients may inflate SI (see Ben-David & Schneider, 2009, for studies on aging in this respect).…”
Section: Discussionsupporting
confidence: 87%
“…P300 latency decreases as children develop (Howard and Polich, 1985;Polich et al, 1990a) and increases with normal aging (Fjell and Walhovd, 2001;Polich, 1996). Component latency also becomes longer as dementia level increases (O'Donnell et al, 1992;Polich and Corey-Bloom, 2005;Polich et al, 1986Polich et al, , 1990bPotter and Barrett, 1999), although few reports suggest how brain insult or disease prolong ERP timing (Bashore and Ridderinkhof, 2002;Polich, 2004).…”
Section: P300 Latencymentioning
confidence: 99%
“…It remains to be seen whether qualitative changes in physiological markers of processing speed are influenced by different cognitive strategies employed by TBI patients or fundamental neuroplastic change to damaged systems or a combination of both. These issues have been addressed elsewhere with respect to TBI and cognitive aging in an excellent review (Bashore and Ridderinkhof, 2002). However, a recent study (Iznak et al, 2010) reported that TBI patients exhibited a shortening of the P300 peak latency after the administration of cerebrolysin, a neurotrophic factor drug that has been shown to promote synaptic repair in animal models (Sharma et al, 2010).…”
Section: Processing Speedmentioning
confidence: 96%